PENGARUH REBUSAN DAUN KATUK UNTUK KELANCARAN PRODUKSI ASI PADA IBU NIFAS DI PMB R TAHUN 2024 - Uswatun Hasanah, Enong; Hadijah, Siti; Nency, Aprilya (Journal of Midwifery Tiara Bunda, 2023)
This study aims to determine the effect of katuk leaf decoction on the smooth production of breast milk in PMB R Year 2024. The research design was quantitative with a pre-experimental design using the one group pretest-posttest desaign approach. The population amounted to 15 postpartum mothers, the technique of taking using total sampling. Data analysis using Univariate Analysis and Bivariate Analysis. Hypothesis testing using Paired T-Test Test. The results of the study before giving the decoction of katuk leaves less breast milk 12 (80%) and smooth breast milk 3 (20%). Whereas after giving a decoction of katuk leaves, breast milk was smooth as much as 11 (73%) and less breast milk 4 (27%). The results of giving cotton leaf decoction before being given treatment in the intervention group obtained an average pretest value of 4.20 to the average posttest value of giving cotton leaf decoction to breast milk production 6.93, the significant value or p value is 0.000 (p < 0.05) so it is concluded that there is an effect of giving cotton leaf decoction on the smooth production of breast milk in postpartum women in PMB R in 2024. In this case, the decoction of katuk leaves will have a gradual effect on the frequency of breastfeeding the baby, and if the decoction of katuk leaves is consumed regularly and regularly, it will be able to increase the milk production of nursing mothers and affect the frequency of breastfeeding the baby.